Ulang Alik, Unik, Puitik: Analisis Puisi-Puisi Karya Soni Farid Maulana - Heri Isnaini (FKIP, Universitas Palangka Raya, 2023)
Literary works are created by literati for their experience and knowledge of life and life. All aspects that are considered interesting and important are immortalized in literary works, both in the form of poetry, prose, and drama. Literati manifest these experiences and knowledge within the framework of social relations where the literati is located. That is, the scope of the literary work created will not be separated from the relationship between the author, the work, and society. Thus, literary works can be viewed prismatically in any point of view and from anywhere. In this paper, literature will be juxtaposed in the corridors of education and religious values in an effort to photograph the relationship between writers and their communities. Literary works were first created aimed at introducing the values of religiosity and divinity. These values are born from the culmination of the literati's awareness of themselves and themselves. In addition, the literary function of “dulce et utile” emphasizes that literary works always have two sides, namely entertainment and education. This function is what places literary works can be explored in terms of educational value and character formation on it. This paper is an attempt at dialogical negotiation between literature, education, and religiosity. The three meet in the same space so that a common thread can be found that covers the supernatural relationship of the three. Thus, this paper is expected to open the insight of thinking on literature as a literary product that can bring divine awareness as well as the formation of educational characters that are beneficial to human life and humanity.